(untitled) (Raparin Journal of Humanities (RJH), 2025)
The paper is an attempt to examine how the common accounting practices, values and professional standards among the accountants of Faruk group determine and affect the level of clarity, by clarity we mean transparency, and the accuracy of financial disclosures. To achieve the objective of this study, the researcher made use of the descriptive analytical methodology in which, the researcher gave out the questionnaire forms to 75 participants which were all chosen on a random basis. As a result, a total of 70 accurate responses were collected and analyzed, which gives a strong response rate of 93.3%. According to our findings, it was found out that accountants possessed a well-developed accounting mindset, with strong conceptual understanding, awareness of international standards, and high ethical principles. Furthermore, throughout the study, a high level of financial transparency, with clear presentation of information and accessibility of key details was found, Pearson’s correlation test affirmed a strong, Sig.nificant positive link between accounting culture and financial disclosure (r = 0.721, Sig. = 0.000). In addition to this, T-tests and ANOVA revealed Sig.nificant variations in accounting culture and financial disclosure based on gender, academic qualifications, and years of experience. In conclusion, the study strongly suggests the continuous support for professional development programs for accountants, this points out the importance of specialized training in global reporting standards and ethical practices, which are certainly essential for improving the clarity and accuracy of financial information provided to relevant parties.